Quality of early childhood education in network hall of conquest of victory of education: a look on the speech of coordinating educational - Relva Lopes Chaves Soares; Sandra Márcia Campos Pereira (Doxa, 2017)
The purpose of this paper is to know the perception of pedagogical coordinators about the quality of EI in municipal Vitória da Conquista education - BA. It is a qualitative research and analysis of the data was from the use of Foucault's postulates: speech, will to truth, knowledge and power. The study reveals that: a) there is line of pedagogical coordinators with the conception of childhood education quality supported in child citizenship; b) the pedagogical coordinators believe that it is possible to guarantee children a public early childhood education quality; c) there is detachment of scientific discourse and political discourse of offering conditions of early childhood education in the municipality of Vitoria da Conquista; d) from Foucault postulates perceive the resistance demonstrated by these coordinators, that despite the working conditions to which they are subjected, act for the sake of improving the quality of early childhood education in day care centers that are under their responsibility.